Determination of amino acids content of the Tagetes lucida Cav. by GC/MS - Liudmyla Slobodianiuk; Liliia Budniak; Svitlana Marchyshyn; Liliya Kostyshyn; Maria Ezhned (Pensoft Publishers, 2021)
Plant raw materials are widely used for the prevention and treatment providing of many diseases. The interest is the in-depth research of the flowers, leaves, and herb of Tagetes lucida. Therefore, the study aimed to determine the content of primary metabolites, namely amino acids in the raw materials of this plant. The amino acids composition and content in flowers, leaves, and herb were determined by the GC/MS method. The results of the study revealed that the raw material of Tagetes lucida contains more bound and less free amino acids. Free and bound L-proline, L-isoleucine were present in all the analyzed samples in the greatest amount (1.909 mg/g and 20.999 mg/g, 0.804 mg/g and 18.908 mg/g in the flowers; 2.721 mg/g and 18.973 mg/g, 3.459 mg/g and 28.518 mg/g in the leaves; 6.436 mg/g and 18.817 mg/g, 0.245 mg/g and 0.222 mg/g in the herb). Another free amino acid with a high content in flowers (1.321 mg/g) and herb (0.825 mg/g) of Tagetes lucida was L-aspartic acid. In addition, high content of L-phenylalanine in bound form was found in the leaves (11.843 mg/g) of the study plant. These amino acids to be considered distinguishing markers of the Tagetes lucida. This research contributes to already known information of Tagetes lucida use as herbal medicine, nutraceutical, and food reinforcement.